Effects of Electroacupuncture on Syt3 and GluA2 in Rats With Limb Spasms After Intracerebral Hemorrhage - Xudong Lu; Huiling Ren; Hequn Chen; Guosheng Shi; Xuanbo Luo; Kai Liu; Qinglin Zhao; Dawei Zhao; Changfa Li; Wei Bu (Brain and Behavior)
ABSTRACT Background Clinical studies have confirmed that electroacupuncture (EA) has the potential to improve spasticity after intracerebral hemorrhage (ICH), yet its precise mechanism remains unclear. Synaptotagmin‐3 (SYT‐3), by mediating the internalization of the glutamate AMPA receptor GLUA2, may be related to EA's mechanism. This study aims to explore the mechanism by which EA improves limb spasticity after ICH, providing scientific evidence for its clinical application. Methods ICH models were established using stereotaxic injection of autologous tail blood into the right striatum. SD rats were randomly divided into Sham, ICH, ICH + SCRAMBLE, EA, and ICH + TAT‐GLUA2‐3Y groups. Rats in the EA group received 30 min of EA treatment daily after ICH. Muscle tone, neurological deficits, and motor function were assessed. After 3 and 7 days of intervention, the motor cortex was dissected for Western blot analysis of SYT‐3, GLUA2, and P‐GLUA2‐Ser880 expression. Immunoprecipitation was used to detect the interaction between SYT‐3 and GLUA2. Nissl staining and NeuN staining were employed to evaluate brain damage. Fluorescence double‐labeling technique was used to observe the expression of SYT‐3 and GLUA2 in the cell membrane and cytoplasm. Transmission electron microscopy was utilized to examine the microstructure of neurons and synapses. Results Compared to the ICH group, rats in the EA group showed reduced muscle tone in the left limbs and significant improvement in neurological deficits and motor function. In the ICH + TAT‐GLUA2‐3Y group, the binding of SYT‐3 and GLUA2 was inhibited, spastic symptoms were alleviated, and membrane expression of GLUA2 increased. In the EA group, SYT‐3 levels were significantly reduced, GLUA2 expression increased in the membrane and cytoplasm, and P‐GLUA2‐Ser880 expression decreased. Rats in the EA group showed increased neuron numbers, normal mitochondrial morphology, and improved synaptic structure in Nissl staining, immunofluorescence, and transmission electron microscopy. Conclusion EA effectively improves limb spasticity following ICH by inhibiting the SYT‐3/GLUA2 pathway.